The economic consequences of an ageing population in Slovenia - Walkenhorst, Peter (OECD Economics Department Working Papers, 2015)
Slovenia's population is set to age rapidly in the coming decades. This demographic trend will increasingly put pressure on already fragile public finances as age related expenditure is projected to rise by 3 percentage points of GDP by the year 2030. Ensuring debt sustainability and generational equity requires reforms of social support systems and necessitates adjustments in labour markets. Policy makers will thus need to act more strongly than in the past to rein in ageing related outlays, pursue efficiency-enhancing restructurings of health and long-term care systems, and adopt measures to strengthen labour force participation. In particular, further increases in the relatively low pension age in line with the rise in life expectancy would reduce pension costs and the burden on the active population. Better utilisation of medical resources and coordinated purchasing of medical supplies would curb health care expenditure, while a dedicated funding mechanism for long-term care would enhance the sustainability of the system. Moreover, removing incentives for early retirement in combination with active labour market policies would increase the labour force participation rates of older workers from its currently very low levels. This Working Paper relates to the 2015 OECD Economic Survey of Slovenia (www.oecd.org/eco/surveys/economic-survey-slovenia.htm)